2015
DOI: 10.1016/j.jagp.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Interpersonal Psychotherapy for Older Adults at Risk for Suicide

Abstract: Objective To pilot a psychological intervention adapted for older adults at-risk for suicide. Design A focused, uncontrolled, pre-to-post-treatment psychotherapy trial. All eligible participants were offered the study intervention. Setting Outpatient mental healthcare provided in the psychiatry department of an academic medical center in a mid-sized Canadian city. Participants Seventeen English-speaking adults 60 years or older, at- risk for suicide by virtue of current suicide ideation, death ideation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…A number of studies have shown that social support influences treatment outcomes in older adults[43, 44]. Other interventions that address interpersonal problems and social isolation may hold particular promise for older adults with limited social support[45-47]. Finally, while disability predicted to treatment outcome at 12 weeks, that effected was not found at 36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that social support influences treatment outcomes in older adults[43, 44]. Other interventions that address interpersonal problems and social isolation may hold particular promise for older adults with limited social support[45-47]. Finally, while disability predicted to treatment outcome at 12 weeks, that effected was not found at 36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Patient centered care requires addressing patient's needs and wants (27), in addition to assessing and targeting standard risk factors (e.g., depression), if present. Older adults who attribute their suicidal behavior to thwarted belongingness may benefit from Interpersonal Psychotherapy (IPT), as an adaptation of IPT for suicidal older adults was found to decrease suicide ideation and increase social support (28). …”
Section: Discussionmentioning
confidence: 99%
“…Cognitive therapy (CT) strategies, which have been adapted for older adults with suicide risk (Bhar & Brown, 2012), could be used to counter the “black and white” thinking that is inherent in labeling oneself a complete burden on others (when in reality our impacts on others are generally mixed and change over time). Interpersonal Psychotherapy (IPT) has also been adapted for older adults with suicide risk (Heisel et al, 2014). IPT’s focus on role transitions could allow older adults who developed perceptions of burdensomeness in the context of increasing functional decline and increasing reliance on others to emotionally process this change in their lives and create more realistic expectations of their interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Current approaches to late-life suicide prevention are limited. Several psychotherapies, including cognitive behavioral therapy (CBT) and interpersonal psychotherapy (IPT) have been adapted for older adults at risk for suicide (Bhar & Brown, 2012; Heisel, Talbot, King, Tu, & Duberstein, 2014). However, interventions for which the study outcome was suicide deaths, such as the TeleHelp-Tele-Check intervention (De Leo, Dello Buono, & Dwyer, 2002), have been largely effective only for women (Lapierre et al, 2011), while in most countries older men are at substantially higher risk.…”
mentioning
confidence: 99%